Istota i założenia optymalizacji podatkowej – wybrane aspekty - Gruziel, Kinga (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
The elaboration presents a literature review concerning a placement of optimization theory in a group of fiscal policy instruments. The research includes literature study from economic scope. In synthetic way discussed the main phase in creating new trends connected with optimization of taxation and its rational principles. The research purposes introduced the analysis of selected tax optimization instruments, which countenance decreasing of tax burden or even avoiding, in fundamental and complex aspect. In accordance with the principles of optimization theory, taxation is a superior aim of fiscal policy – maximization of social prosperity, which is possible to attain through selection of optimal variant of taxation. The principles of optimization taxation theory is useful for state budgets and for individual business entity